EFISIENSI PEMASARAN CABAI MERAH MELALUI PASAR LELANG SPOT DI KABUPATEN KULONPROGO, YOGYAKARTA - Jamhari, Ebban Bagus Kuntadi, (Jurnal Social Economic of Agriculture, 2012)
Red Chili is a seasonal product which is close to price fluctuation.Price fluctuation is one of market phenomenon that oftentimes has to befaced by horticulture farmer. About main problem that always faced isbargaining position by farmer is low, price information isnt transmitted verywell, not good on quality and the long of distribution chain. Inefficiency onmarketing system will get crescent other wising to strengthen farmersbargaining position. One of the efforts which can be done by the farmer tostrengthen bargaining position is using Spot Auction Market System.The objectives of the research are: 1). Knowing how long thedistribution channel of red chili between through and not through spotauction market, 2) Knowing marketing efficiencies of red chili betweenthrough and not through spot auction market, 3) Describes about spotauction market of red chili.The method of this research is descriptive analytic method. Thisobservational location determined by purposive method. Sampling method inthis research used by multistage random sampling. The first objectiveanalyzed by use descriptive analysis, meanwhile second objective analyzedwith monopoly index (MPI).The result of this research are the distribution channel on red chilithrough spot auction market was farmer sells to collecting trader and thancollecting trader sells to wholesalers and wholesalers sells to retailer andfinally retailers sells to consumers. Index monopolizes between red chilimarketing through auction market is as big as 1,51. Its mean that red chilimarketing through spot auction market is efficient based on monopoly index.Keyword : Pasar Lelang, Rantai Pemasaran, Efisiensi Pemasaran